Role of enzymes catalase, peroxidase and amino acid (proline) in Raphanus sativus and Lepidium sativus in exposure levels different water pollution of ion lead - Oudah, Husham K.; Jawad, Mokdad M.; Abed, Eman H. (Iraqi Journal of Science, 2022)
Radish (Raphanus sativus L.) and (Lepidium sativus) is commonly grown in urban and suburban areas where the soil may be polluted with heavy metal such as lead. In this study, short exposure of radish and cress plantlets to (0,10,20,30,50)ppm lead in nutrient solution (three months) in growth chamber conditions elicited an antioxidative response, measured in terms of lipid peroxidation, protein and proline accumulation and peroxidase and Catalase activity. Longer exposure to lead when radish and cress was grown outdoors for 90 days in pots filled with field soil with different lead content also resulted in higher lipid peroxidation and proline accumulation and altered protein content and enzyme activity. The results also showed significant decrease antioxidant enzymes activity with the decreased oxidative stress. Also, the antioxidant enzymes activity (CAT and POD) were more activity after 30 days because of resistant for (50 ppm ,30 ppm) . Besides, at high level, the response of the antioxidant enzymes activity (CAT and POD) and proline accumulation were similar to that observed in control treatment. The highest proline content (81and 96 μmole/g) were recorded by control treatment after 30days radish and cress, respectively. The maximum average increase in peroxidase activity (43.76 and 68.38 unit/ml) were though control level treatment after 30 days, respectively. Maximum results were found in treatments (56.25 and 56.52 unit/ml) after 30 days in radish and cress, respectively.